KHADIRARISHTA: A MEDICAL REVIEW - Shinde, Rashmi Rajendra; Bhangale, Kirti (International Journal of Research -GRANTHAALAYAH, 2017)
In sushrut samhita chikitsa6/19 it has been mentioned that khadira is effective in all type of kushta. Khadirarishta is a very effective Arishta in the treatment of skin diseases specially Ekakushta. It contains 5-10% of self-generated alcohol in it. It mainly contains Khadira which is potent krumighna and kandughna dravya.